Group dynamics in Canadian recreational team sports later in life. (May 2022) - Gayman, Amy M.; Eys, Mark; Coleman, Taylor
Abstract: As interest and participation in physical activity later in life increases, evidence is needed to inform the promotion, design, and delivery of community-based sport for older people. One important consideration is the dynamics of the group, which may influence experiences of team sport among aging populations. A qualitative study was undertaken to explore group dynamics concepts and perceived outcomes experienced by older adults involved in Canadian community-based recreational teams. Seventeen mid-life and older adults ( M age = 64.06, SD = 6.40) who previously participated in youth team sport and were currently involved in adult recreational team sport participated in semi-structured phone interviews. Results were organized into categories outlined in the conceptual framework for the study of sport teams (Eys et al., 2020). Issues specific to team dynamics experienced in older adulthood are highlighted and relate to competitiveness, sport specific skills/knowledge, competitive level, motivational climate, interdependence, team stability, group norms, roles, cohesion, leadership, social support, conflict, enjoyment, personal development, and social connections. Findings underscore the relevance of team dynamics in older adulthood and importance of understanding individual and environmental attributes in relation to group processes, structures, emergent states, and outcomes specific to sport for older adults. Directions for future research and practical implications to encourage greater involvement and sustained participation in team sport throughout the lifespan are discussed. Graphical abstract: Image 1 Highlights: Group dynamics are important to team sport regardless of age or level of involvement. The conceptual framework for sport teams is used to study older adult participation. Group dynamics factors and outcomes in older adult team sports are explored. Additional research in the area of group dynamics later in life is recommended.